2014
DOI: 10.1021/ph500316u
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Structural Engineering of Nanoporous Photonic Structures: Tailoring Nanopore Architecture to Enhance Sensing Properties

Abstract: In this study, we demonstrate that an optimal design of the pore geometry and shape of sensing platforms based on nanoporous anodic alumina (NAA) photonic structures is critical to develop optical sensors with improved capabilities. To this end, two types of NAA photonic structures featuring different pore geometries (i.e., pore lengths and diameters) and shapes (i.e., straight and modulated pores) were produced, and their optical characteristics were assessed systematically by reflectometric interference spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 48 publications
2
61
0
Order By: Relevance
“…[22][23][24][25][26][27][28] Recently, some of these approaches have been used to produce numerous NAA-based photonic structures, including rugate filters, optical microcavities, FabryPerót interferometers and distributed Bragg reflectors. [29][30][31][32][33][34][35][36][37][38][39] The development of optical platforms based on NAA has spread the use of this nanomaterial, typically used as a nanoporous template to grow other nanostructures such as nanowires and nanotubes 15 , towards more relevant applications such as optical sensing systems, drug delivery chips and photonic tags. [40][41][42][43][44][45][46][47][48][49][50][51] In this study, we present an innovative and rationally designed pulse anodisation approach, so called pseudo-stepwise pulse anodisation (PSPA), which enables the fabrication of nanoporous anodic alumina optical bandpass filters (NAABPFs) with advanced optical properties (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Recently, some of these approaches have been used to produce numerous NAA-based photonic structures, including rugate filters, optical microcavities, FabryPerót interferometers and distributed Bragg reflectors. [29][30][31][32][33][34][35][36][37][38][39] The development of optical platforms based on NAA has spread the use of this nanomaterial, typically used as a nanoporous template to grow other nanostructures such as nanowires and nanotubes 15 , towards more relevant applications such as optical sensing systems, drug delivery chips and photonic tags. [40][41][42][43][44][45][46][47][48][49][50][51] In this study, we present an innovative and rationally designed pulse anodisation approach, so called pseudo-stepwise pulse anodisation (PSPA), which enables the fabrication of nanoporous anodic alumina optical bandpass filters (NAABPFs) with advanced optical properties (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Rationally designed electrochemical approaches have recently shown that biomimetic photonic films based on nanoporous anodic alumina (NAA) generated on the surface of aluminum by anodization could overcome the limitations of current metal coloring processes through eco-friendly fabrication approaches. [17][18][19][20] NAA photonic films can reflect light at specific wavelengths within the UV-visible-NIR spectrum by interferometric phenomenon, which in turn results in aluminum pieces displaying vivid and bright colors. [21][22][23][24][25][26][27][28] The color of these anodic films can be tuned across the UV-visible-NIR spectrum by engineering their photonic stop band through the internal nanoporous structure, without the use of toxic chemical compounds or additional fabrication stages.…”
Section: Introductionmentioning
confidence: 99%
“…The same approach has been also demonstrated to the detection of Hg 2+ ions in water wit a limit of detection of 1 μM. Finally, a comparison between the two RIfS methods presented in this section can be found in [129] and more detailed reviews on these applications in [130,131].…”
Section: Reflection Interference Spectroscopymentioning
confidence: 95%